Financing India's disaster risk resilience strategy - Saon Ray; Samridhi Jain; Vasundhara Thakur (Indian Council for Research on International Economic Relations (ICRIER), 2021)
In this paper, we try to cover a whole range of polices and schemes that have been undertaken in Indiato finance disaster risk resilience (DRR). This paper tries to emphasise the importance of DRR in dealing with natural catastrophesby integrating DRR and climate change adaptation strategies for the purpose of mainstreaming them into centrally sponsored schemes. It briefly talks about synergising risk reduction efforts with sustainable development goals through the Sendai Framework. This framework calls for all-inclusive collective action from private stakeholdersandlocal governments,while unambiguously stating the primary role of a state. The paper reflects briefly on the gaps since the advent of these policies and suggests methods for financing based on experiences of other countries. Then the focus of the paper shifts towards insurance and reinsurance mechanisms used in other countries for financing these catastrophes. It underlines a concept that resilience can be attained only through building better infrastructure for reducing shocks and these instruments can be financed by introducing new financial tools which deal with climate change from its very inception. Infrastructure creation is an ineluctable component of economic growth and development. It points out that the success of any economy is heavily dependent on its infrastructure network and assets -existing and planned -and ignoring the 'resilience' aspect in infrastructure management and investment would mean additional vulnerabilities and serious negative impacts on efforts towards sustainable development and a low carbon future.Scaling up resilient infrastructure will also bring numerous co-benefits by diffusing development across sectors.Despite the suite of reforms that have been initiated in shifting towards resilient infrastructure and disaster funds,implementation of these reformshasbeen poor. These reforms are stalled by the weakness in execution and layers and sub-layers involved indelivering these services.
Keywords: Q54; G22; G32; 330; financing; disaster risk resilience; Sendai Framework; insurance; build back better